2019
DOI: 10.5194/esd-2019-21
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate System Response to Stratospheric Sulfate Aerosols: Sensitivity to Altitude of Aerosol Layer

Abstract: Abstract. Reduction of surface temperatures of the planet by injecting sulfate aerosols in the stratosphere has been suggested as an option to reduce the amount of human-induced climate warming. Several previous studies have shown that for a specified amount of injection, aerosols injected at a higher altitude in the stratosphere would produce more cooling because aerosol sedimentation would take longer time. In this study, we isolate and assess the sensitivity to the altitude of the aerosol layer of stratosph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Studies have shown that multiple mitigation targets could be achieved by adjusting the injection latitude and amount of sulfate aerosol injections (e.g., Kravitz et al, 2017; MacMartin et al, 2017; Tilmes et al, 2017). Changes in the aerosol distributions could alter the regional climate response and affect the land carbon response (e.g., Krishna‐Pillai Sukumara‐Pillai et al, 2019; Tilmes et al, 2017). Changes in the aerosol size may also affect the scattering effect of aerosol particles (Krishnamohan et al, 2020) and influence partitioning of solar radiation to direct and diffuse components (Eck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that multiple mitigation targets could be achieved by adjusting the injection latitude and amount of sulfate aerosol injections (e.g., Kravitz et al, 2017; MacMartin et al, 2017; Tilmes et al, 2017). Changes in the aerosol distributions could alter the regional climate response and affect the land carbon response (e.g., Krishna‐Pillai Sukumara‐Pillai et al, 2019; Tilmes et al, 2017). Changes in the aerosol size may also affect the scattering effect of aerosol particles (Krishnamohan et al, 2020) and influence partitioning of solar radiation to direct and diffuse components (Eck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the climate response will be different for volcanic eruptions at different seasons or latitudes as high‐latitude eruptions would cause large hemispheric energy imbalance (e.g., Haywood et al, ; Pausata et al, ; Stevenson et al, ). Different deployment strategies of stratospheric aerosol geoengineering would also cause different climate changes (e.g., Kleinschmitt et al, ; Krishna‐Pillai Sukumara‐Pillai et al, ; Simone Tilmes et al, ). Robock et al () emphasized that the observed climate change from volcanic eruptions cannot be directly used to infer the climate response of continuous stratospheric sulfate aerosol injection geoengineering.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the addition of sulfate aerosols into the stratosphere could offset the CO 2 -induced global mean warming but usually at the cost of a reduced intensity of global hydrological cycle mainly associated with the fast climate adjustments (e.g., Duan et al, 2018;Ferraro & Griffiths, 2016;Kalidindi et al, 2015;Myhre et al, 2018). Also, stratospheric aerosol geoengineering can induce changes in stratospheric ozone concentration and large-scale stratospheric circulation due to the change in stratospheric temperature, water vapor content, and heating rate (Ferraro et al, 2015;Kalidindi et al, 2015;Krishna-Pillai Sukumara-Pillai et al, 2019;Madronich et al, 2018;Nalam et al, 2017;Pitari et al, 2014;Richter et al, 2017;Simone Tilmes et al, 2009). A number of recent studies have shown that multiple temperature goals could be achieved by interactively adjusting the location and rate of sulfate aerosol injections, indicating the possibility to achieve multiple regional climate mitigation goals (e.g., Kravitz the climate response, SAI geoengineering has been simulated with multiple climate models using the same experimental protocol under the framework of the Geoengineering Model Intercomparison Project (e.g., Kravitz et al, 2011Kravitz et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Process-level studies can reveal mechanistic understanding; for example, simulations that prescribe or turn off longwave radiative heating 47,82 can explore the effects of stratospheric heating on surface climate, revealing and isolating mechanisms of change. Idealized simulations investigating how the altitude of injection influences stratospheric heating may further inform the importance of these effects 83 . Model intercomparisons (for example, the Geoengineering Model Intercomparison Project (GeoMIP) 84 ) also offer useful insight, particularly with understanding the similarities and differences between responses to standardized modelling experiments.…”
Section: Basis For Confidencementioning
confidence: 99%